Woman's songs in ancient Greece - Klinck, Anne L., 1943- (McGill-Queen's University Press, 2008)
By considering women's voices in performance, Anne Klinck provides a new perspective on women's "writing." She shows that our understanding of femininity in ancient Greece can be expanded by going beyond poetry composed by women poets like Sappho to explore girls' and women's choral songs from the archaic period, songs for female choruses and characters in tragedy, and lyrical representations of women's rituals and cults.